Enhancing Students’ Mathematical Critical Thinking Skills through a GeoGebra Integrated Project-Based Learning Model - Setyawan, Dedy; Anas, Aswar; Nasir, A. Muhajir; Fadly, Dewiyanti (Journal of Ecohumanism, 2024)
This study investigates the efficacy of the Project-Based Learning (PjBL) paradigm integrated with GeoGebra in fostering students’ critical thinking skills in mathematics. Utilizing a quasi-experimental design, two groups were compared: the experimental group received instruction via the GeoGebra-integrated PjBL model, while the control group followed a traditional explanatory approach. Data were collected through pretest and posttest assessments of mathematical critical thinking skills. Statistical analyses, including an independent samples t-test, revealed a significant improvement in the experimental group compared to the control group (p < 0.05, significance value 0.000). The N-Gain test categorized the intervention as "quite effective." These findings demonstrate that the GeoGebra-integrated PjBL model substantially enhances students’ mathematical critical thinking abilities compared to conventional teaching methods. This study highlights the pedagogical implications for mathematics education, advocating for broader implementation of innovative teaching strategies that integrate digital tools.